Buku Pop-Up Sebagai Media Untuk Mengenalkan Museum Sultan Mahmud Badaruddin II di Kota Palembang - Muhammad, Nur; Mubarat, Husni (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
This design stems from the problem of the lack of promotion of museums to children, especially aged 6-12 years in Palembang City. Children's lack of interest in visiting museums is also directly influenced by the development of technology and the internet. Museums also have an educational role in conveying educational missions to children. Through pop-up books, children can imagine museums from a fun perspective. This design aims to provide education and foster children's interest in visiting museums, especially the Sultan Mahmud Badarudin II Palembang museum. which holds a lot of history or history about the city of Palembang. This design uses the 5W 2H (What, Who, Where, When, Why, How, How To Much) data analysis method. The main media used in this design is a Pop Up book, while the supporting media consists of posters, drink bottles, bag hangers, T-Shirts and bag hangers. By designing a pop-up book to introduce the Sultan Mahmud Badarudin II museum, it is hoped that the public, especially children aged 6-12 years and also the nation's generation, will enjoy getting to know the museum interactively through pop-up book visuals and getting to know the history and culture of their ancestors. as a learning medium in the future.